PHILOSOPHY AND CULTURAL VALUES OF THE DESA DAYAK SUB-TRIBE IN SHIFTING AGRICULTURE - Pether Sobian; Markus M.Si (Universitas Kapuas Sintang, 2024)
This research is motivated by the author's desire to describe the facts of shifting agriculture the Dayak Desa sub-tribe. Shifting agriculture is not just an activity of burning land, planting rice or harvesting. Shifting agriculture has spiritual values, culture, local wisdom and togetherness. Shifting agriculture is part of the belief that is manifested in the form of a farming ritual system. The purpose of this study is to describe shifting agriculture practices that have been carried out from generation to generation for hundreds of years. There are 9 (nine) stages of shifting agriculture starting from the beginning, namely slashing (manggul) to the end, namely harvesting (ngetaw) which should be carried out by cultivators of the Dayak Desa sub-tribe: 1). Manggul. 2). Nebash. 3). Nebang. 4. Ngeladaq (cleaning the edge of the field so that the fire cannot spread out of the field). 5). Nunu (to burn) . 6). Nayaq. 7). Nugal. 8). Ngemabaw (cleaning the field by pulling the grass). 9). Ngetaw (harvesting rice). Shifting agriculture in the Dayak Desa sub-tribe version has at least 10 cultural values. These values ​​are; Foraging for food, spirituality, togetherness, caring for the environment, local wisdom (cultivation), Ethics and Law, Joy and gratitude, New Year's Eve and property rights. Terminology in English that is used to designate the farming activities of the Dayak people and especially the Dayak Desa sub-tribe such as the word 'slash and burn' is inaccurate and can lead to misleading interpretations. The Dayak Desa sub-tribe community does not slash land and then burn it, it is true that there are slashing and burning activities in farming activities, but the term 'slash and burn' is not appropriate when used for farming activities. Slashing and burning activities can also be done without farming. The terms slashing and burning are wrong terms so that it can lead to a wrong understanding of farming activities. The English terminology that is closer to the fact of farming activity is 'Shifting Agriculture'